Readiness of Local Government in the Implementation of Accrual Accounting: The Case of Local Government in Aceh, Indonesia - Mirna Indriani; Ratna Mulyany; Nadirsyah Nadirsyah; Wahyu Munandar (Jurnal Dinamika Akuntansi dan Bisnis, 2018)
This study aims to examine the influence of human resources, information technology, and organizational culture on Indonesian local governments’ readiness in implementing accrual accounting system. The hypotheses were tested by using quantitative approach with the utilization of survey method. The unit of analysis consists of 52 working units of government institution in Aceh, Indonesia. Simple random sampling technique was employed and a total of 92 respondents participated in the survey. The result shows that human resources and information technology influence government readiness in implementing accrual accounting while organizational culture does not. The findings of this study imply that the government entities need to further strengthen its human resource and information technology to fully support the successful implementation of accrual based accounting system.